2010
DOI: 10.1590/s0036-36342010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a la demanda de servicios para la atención del parto en México

Abstract: The utilization of an institution of delivery that differed from the one with which the women were affiliated indicates the existence of a de facto functional integration between health institutions in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…Seguro Popular impact assessment studies have demonstrated its protective effect against catastrophic health spending among its beneficiaries [12]–[14], [16][18], and analyses on health care utilization have sighted a number of contributions [19], [20]. However, evidence regarding performance in rural indigenous communities at the lowest economic levels [21], [22] suggests that results have been less favorable among these beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…Seguro Popular impact assessment studies have demonstrated its protective effect against catastrophic health spending among its beneficiaries [12]–[14], [16][18], and analyses on health care utilization have sighted a number of contributions [19], [20]. However, evidence regarding performance in rural indigenous communities at the lowest economic levels [21], [22] suggests that results have been less favorable among these beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these actions have been documented: SP financing has enhanced the possibility for women to attend at least four antenatal care appointments and to receive birth care by trained personnel . Furthermore, SP enrollment has increased access to health care for women with lower schooling, reducing their risk for preterm birth .…”
Section: Introductionmentioning
confidence: 99%
“…The results of these actions have been documented: SP financing has enhanced the possibility for women to attend at least four antenatal care appointments 4 and to receive birth care by trained personnel. 5,6 Furthermore, SP enrollment has increased access to health care for women with lower schooling, reducing their risk for preterm birth. 7 On the negative side, however, it has been noted that service production varies significantly among states with comparable public expenditure, particularly as regards to the delivery of opportune and frequent antenatal care with adequate content.…”
Section: Introductionmentioning
confidence: 99%
“…However, Levy-Algazy [ 5 ] reported that, within a one-year period between 2005 and 2006, up to 20% of IMSS workers moved from the formal labour market segment to informality or to economic inactivity, thus losing access to IMSS healthcare. Furthermore, insured workers often utilise private healthcare providers or Ministry of Health facilities, leading to service duplication, high out-of-pocket expenditure and decreased incentives to improve insured services [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%